On the Affine Weyl group of type A˜n−1 - Muhammad A. Albar (International Journal of Mathematics and Mathematical Sciences)
We study in this paper the affine Weyl group of type A˜n−1, [1]. Coxeter [1] showed that this group is infinite. We see in Bourbaki [2] that A˜n−1 is a split extension of Sn, the symmetric group of degree n, by a group of translations and of lattice of weights. A˜n−1 is one of the crystallographic Coxeter groups considered by Maxwell [3], [4].